Analysis Tool For Semantic Web Ontology - Selathurai, Asha Devi (2006)
Ontology language(OWL) is the backbone of the Semantic Web. Reading an OWL file and trying to understand the ontology it represent s is a hefty and tedious task. This report presents a tool that is used to analyze and processes the OWL files.